TANTANGAN MAHASISWA PENDIDIKAN TEKNIK MESIN DALAM MENJAGA KONSISTENSI DISIPLIN KEISLAMAN DAN PENDIDIKAN - Farrij Rizqi Fadhillah; Muhammad Wildan Firdaus; Raihan Musthofa Zahrani; Jenuri (JCI Publisher, 2026)
Mechanical Engineering Education (PTM) demands logical precision and mastery of high technology, creating an intensive academic burden for students. This condition often leads to an invisible dichotomy between